Comparison of organic peracids in wastewater treatment: Disinfection, oxidation and corrosion. (15th November 2015) - Luukkonen, Tero; Heyninck, Tom; Rämö, Jaakko; Lassi, Ulla
Abstract: The use of organic peracids in wastewater treatment is attracting increasing interest. The common beneficial features of peracids are effective anti-microbial properties, lack of harmful disinfection by-products and high oxidation power. In this study performic (PFA), peracetic (PAA) and perpropionic acids (PPA) were synthesized and compared in laboratory batch experiments for the inactivation of Escherichia coli and enterococci in tertiary wastewater, oxidation of bisphenol-A and for corrosive properties. Disinfection tests revealed PFA to be a more potent disinfectant than PAA or PPA. 1.5 mg L −1 dose and 2 min of contact time already resulted in 3.0 log E. coli and 1.2 log enterococci reduction. Operational costs of disinfection were estimated to be 0.0114, 0.0261 and 0.0207 €/m 3 for PFA, PAA and PPA, respectively. Disinfection followed the first order kinetics (Hom model or S-model) with all studied peracids. However, in the bisphenol-A oxidation experiments involving Fenton-like conditions (pH = 3.5, Fe 2+ or Cu 2+ = 0.4 mM) peracids brought no additional improvement to traditionally used and lower cost hydrogen peroxide. Corrosion measurements showed peracids to cause only a negligible corrosion rate (<6 μm year −1 ) on stainless steel 316L while corrosion rates on the carbon steel sample were significantly higher (<500 μm year −1 ). Graphical abstract: Highlights: Performic acid was more potent disinfectant than peracetic or perpropionic acid. No additional benefit in Fenton-like oxidation when compared to hydrogen peroxide. Corrosion on carbon steel was 100-fold higher than on stainless steel 316L.